The Hazard of Merger by Absorption – Why Some Knappschaften Merged and Others Did not: 1861–1920 - Tobias Alexander Jopp (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
By the mid-19th century, following the Prussian mining reform, German miners' combined mutual health and pension funds took on the characteristics of social insurance and underwent a concentration process driven by mergers, liquidations, and unequal internal growth. This paper investigates the determinants of mergers by absorption among Prussian funds combined with quantitative evidence from a regression model, provides new insights into the first social-insurance merger wave in Germany. While most contemporary sources convey the impression that funds were merged to stabilize the entire insurance scheme by sorting out actuarially unviable and financially distressed funds, statistical evidence suggests that funds were absorbed over time primarily because they offered advantages to the absorbing fund and, hence, were quite attractive targets. – – Um die Mitte des 19. Jahrhunderts übernahmen die kombinierten Kranken- und Pensionskassen der deutschen Bergleute die Funktion einer Sozialversicherung und durchliefen im den folgenden Dekaden einen insbesondere durch Fusionen und Schließungen gekennzeichneten Konzentrationsprozess. Dieser Aufsatz untersucht die Determinanten der Fusionen im preußischen Knappschaftswesen aus der Sicht der übernommenen Kassen unter Rückgriff auf ein der Duration Analysis entlehnten Regressionsmodells. Während zeitgenössische Quellen überwiegend den Eindruck vermitteln, dass Knappschaftsvereine fusioniert wurden, um das Versicherungssystem insgesamt zu stabilisieren, deuten die Befunde der quantitativen Analyse darauf hin, dass in erster Linie solche Knappschaftsvereine übernommen wurden, die für die Wachsttumsstrategie des übernehmenden Vereins von Vorteil waren.
Keywords: C41; G22; G23; I31; N33; 330; competing risk; financial distress; insurance; Knappschaft; liquidation; merger; mining